2023
DOI: 10.3390/agriculture13122265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gender and Muscle Type on Fatty Acid Profile, Sanogenic Indices, and Instrumental and Sensory Analysis of Flemish Giant Rabbit Meat

Gabriela Frunză,
Marius-Mihai Ciobanu,
Otilia Cristina Murariu
et al.

Abstract: The aim of this study was to represent quality characterization, by gender and muscle type, of rabbit meat from the Flemish Giant (FG) breed, following the fatty acid profile, sanogenic indices, and instrumental (color and texture) and sensory analysis. The biological material comprised 40 rabbits (20 females and 20 males) whose Longissimus dorsi (LD) and Semimembranosus (SM) muscles were sampled. Compared to female samples, the meat from males was more qualitative in terms of higher ratios of polyunsaturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…In response to the growing emphasis on the quality of products of animal origin, Frunză et al [24] investigated the effect of gender and muscle type on the fatty acid profile, health lipid indices, texture, color, and sensory quality of rabbit meat. Research has shown that male meat was healthier (richer in essential fatty acids, with a better ratio of hypo-/hypercholesterolemic fatty acids and lower values of atherogenic indices (AIs) and thrombogenic indices (TIs)).…”
mentioning
confidence: 99%
“…In response to the growing emphasis on the quality of products of animal origin, Frunză et al [24] investigated the effect of gender and muscle type on the fatty acid profile, health lipid indices, texture, color, and sensory quality of rabbit meat. Research has shown that male meat was healthier (richer in essential fatty acids, with a better ratio of hypo-/hypercholesterolemic fatty acids and lower values of atherogenic indices (AIs) and thrombogenic indices (TIs)).…”
mentioning
confidence: 99%